Regular reassessment of bleeding risk using the HAS-BLED score reduces bleeding outcomes in a prospective cohort: a report from the mAFA II clinical trial extension. (25th November 2020) - Guo, Y; Lane, D; Chen, Y; Lip, G.Y.H
Abstract: Background: The HAS-BLED score was introduced to draw attention to modifiable bleeding risk factors and to identify patients with atrial fibrillation (AF) at high-risk of bleeding for early review and follow-up. The mAFA-II randomised trial reported that a holistic management strategy using App-based mobile Health technology support reduced AF-related adverse outcomes, compared to usual care. Objective: To assess whether regular reassessment of bleeding risk using the HAS-BLED score would improve bleeding outcomes and oral anticoagulation (OAC) uptake. Methods: Data for this analysis was drawn from the mAF App intervention arm. Bleeding risk (HAS-BLED score) and stroke risk (CHA2DS2-VASc score) were monitored prospectively using mAFA, and calculated during 4 periods: 1–30 days, 31–60 days, 61–180 days, and 181–365 days. Clinical events and OAC changes in relation to the dynamic monitoring and reassessments were analysed. Results: We studied 1793 patients with AF (mean age 64 years, 32.5% female). The average number of re-assessments of CHA2DS2-VASc and HAS-BLED scores were 6.8 (SD 4.0) and 6.8 (4.1), respectively. Comparing baseline and 12 months, the proportion of AF patients with HAS-BLED ≥3 decreased (11.8% vs. 8.5%, p=0.008), with changes in use of concomitant NSAIDs/antiplatelets, renal dysfunction, and labile international normalized ratio (INR) contributing to the decreased proportion of patients with HAS-BLED ≥3 temporally (p<0.05). Use of non-vitamin K antagonist oral anticoagulants (NOAC), warfarin, and any antiplatelet drug was 47.1%, 13.8%, and 15.5%, respectively, at baseline. Incident bleeding events decreased significantly from 1–30 days to 181–365 days (1.2% to 0.2%, respectively; Table 1). Warfarin and NOAC use increased significantly over this period (17.9% to 18.4% and 46.4% to 51.8%, respectively). Conclusion: In this clinical trial cohort, dynamic risk monitoring and reassessment using the HAS-BLED score, together with holistic App-based management using mAFA II reduced bleeding events, addressed modifiable bleeding risks and increased uptake of OACs. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation of China (H2501), NIHR Global Health Research Group on Atrial Fibrillation management